Reptile predators of swiftlets (genus Aerodramus), with a focus on their impact on the swiftlet farming industry - Evan, Quah Seng Huat; Chong, Ju Lian (Department of Biology Victor Valley College, 2023)
We conducted a comprehensive review of literature and online records to determine the extent of reptile predation on swiftlets (genus Aerodramus), especially on commercially farmed species. Reptiles appear to be a large component of reported swiftlet predators, including six species of lizards and 16 species of snakes representing eight families and 17 genera. Predation events have been reported from India, Peninsular Malaysia, Borneo, Indonesia, and Australia. The presence of reptile predators may negatively impact production at swiftlet farms and lead to human-wildlife conflicts. Additional research is needed to find mitigation measures so that industry stakeholders can coexist with reptiles. Further studies will likely identify additional species of reptile predators of swiftlets.